Characteristics of meniscus progenitor cells migrated from injured meniscus. Issue 9 (12th December 2016) - Seol, Dongrim; Zhou, Cheng; Brouillette, Marc J.; Song, Ino; Yu, Yin; Choe, Hyeong Hun; Lehman, Abigail D.; Jang, Kee W.; Fredericks, Douglas C.; Laughlin, Barbara J.; Martin, James A.
ABSTRACT: Serious meniscus injuries seldom heal and increase the risk for knee osteoarthritis; thus, there is a need to develop new reparative therapies. In that regard, stimulating tissue regeneration by autologous stem/progenitor cells has emerged as a promising new strategy. We showed previously that migratory chondrogenic progenitor cells (CPCs) were recruited to injured cartilage, where they showed a capability in situ tissue repair. Here, we tested the hypothesis that the meniscus contains a similar population of regenerative cells. Explant studies revealed that migrating cells were mainly confined to the red zone in normal menisci: However, these cells were capable of repopulating defects made in the white zone. In vivo, migrating cell numbers increased dramatically in damaged meniscus. Relative to non‐migrating meniscus cells, migrating cells were more clonogenic, overexpressed progenitor cell markers, and included a larger side population. Gene expression profiling showed that the migrating population was more similar to CPCs than other meniscus cells. Finally, migrating cells equaled CPCs in chondrogenic potential, indicating a capacity for repair of the cartilaginous white zone of the meniscus. These findings demonstrate that, much as in articular cartilage, injuries to the meniscus mobilize an intrinsic progenitor cell population with strong reparative potential. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1966–1972, 2017.